The Effect Of Substitute Of Kangkung Extract On The Quality Of Wet Noodles - Oktaviani, Rima; Faridah, Anni (Universitas Negeri Padang, 2022)
The background of this research is that the water spinach extract used in food processing is not optimal, while the water spinach extract can be an alternative for additional ingredients in the manufacture of wet noodles. This study aims to analyze the effect of substitution of the addition of kale extract with treatments of 0%, 15%, 30%, 45%. On the quality of shape, color, aroma, texture and taste. This type of research is a pure experiment using a completely randomized design method. It was repeated three times with 5 semi-trained panelists, which was held at the Workshop on Catering at the Department of IKK, FPP, UNP. The dependent variable (Y) is the quality of wet noodles. The instrument used was an organoleptic test through a level test, using ANOVA statistics and if it was significantly different, it was continued with Duncan's test. The results showed that there was a significant effect on the quality of color, aroma and taste. While the neat shape and slightly chewy texture have no significant difference. It can be concluded that the best percentage is found without the addition of kale extract on the quality of wet noodles.